Employment Rates for People with and without Disabilities. Data Note. Number 63 / John Shepard. - Shepard, John (Distributed by ERIC Clearinghouse, 2019)
Data show that people with disabilities are consistently less likely to be working than their non-disabled counterparts. In this Data Note, the employment rate for working-age people is compared across disability types, as well as those without disabilities. While employment rates across disability subpopulation groups vary, all disability groups lag far behind their counterparts without a disability. The employment rates by subpopulation underscore the challenges faced by specific groups in obtaining and retaining employment. Closing the employment rate gap between working-age people in various disability subpopulations and their working-age counterparts without disabilities should be a critical goal for policy and practice. [This is a publication of StateData.info, a project of ThinkWork at the Institute for Community Inclusion, University of Massachusetts Boston.]